Thermal Diffusivity Measurement of Abrasive Paper Using Photoacoustic Technique - Wan Yusoff, Wan Yusmawati; Mat Yunus, W. Mahmood (Universiti Putra Malaysia Press, 2003)
Measurements of thermal diffusivity of two types of abrasive papers are reported. We have chosen silicon carbide and aluminium oxide abrasive papers as our samples. Thermal diffusivity of silicon carbide abrasive paper with the grit size of 320,360,400, 600, 800, 1000, 1200, and 1500 were measured. On the other hand, only two grit size (120 and 240) of aluminium oxide abrasive papers were chosen in the present experiments. All the measurements were carried out at room temperature with the abrasive surface facing the laser beam. The effective thermal diffusivity values obtained for silicon carbide are in the range of (5.1 - 8.9) x 10-2 cm2/s, which is lower than the value of thermal diffusivity of pellet ceramic silicon carbide prepared from silicon carbide powder. For aluminium oxide abrasive papers the effective value of thermal diffusivity (0.18 cm2/s dan 0.35 cm2/s) is higher than the value reported for aluminium oxide ceramic. The surface structure of the sample was investigated using SEM with the magnification of 100X.